The impact of physical activity intervention on perinatal depression: A systematic review and meta-analysis - He, Liping; Soh, Kim Lam; Huang, Feifei; Khaza'ai, Huzwah; Geok, Soh Kim; Vorasiha, Ponpun; Chen, Aixiang; Ma, Jiangping (Elsevier BV, 2023)
Background: No meta-analysis has analyzed the effect of physical activity level, period of physical activity intervention, and duration of intervention, on perinatal depression. This study was to evaluate the impact of physical activity intensity, dose, period, and duration on perinatal depression. Methods: The literature was searched via the PubMed, Embase, Cochrane Library, and Web of Science databases. Weighted mean difference (WMD) or the risk ratio (RR) was used as the effect indicator, and the effect size was represented by the 95 confidence interval (CI). Subgroup analysis based on the perinatal stage, physical activity intensity, physical activity equivalent, and intervention duration was performed. Results: Totally, 35 studies including 5084 women were included. Physical activity could reduce the incidence and severity of depression in perinatal women. Among depressed women with prenatal depression, low-intensity physical activity, with metabolic equivalents (METs)-min/week being <450, was associated with lower levels of depression. In the general population, the risk of postpartum depression was lower in the physical activity group when the duration of intervention was ≥12 weeks, being II, III stage, and ≥450 METs-min/week. Both low and moderate-intensity physical activity were beneficial to an improved depression severity among depressed women with postpartum depression, and moderate exercise intervention could decrease the risk of postpartum depression in general pregnant women. Limitations: Different types of physical activities may affect the effectiveness of interventions. Conclusion: Our study indicated physical activity specifically targeted at pregnant women could reduce depression risk and severity.